2013
DOI: 10.1002/term.1725
|View full text |Cite
|
Sign up to set email alerts
|

Towards embryonic-like scaffolds for skin tissue engineering: identification of effector molecules and construction of scaffolds

Abstract: Autologous skin grafts are the gold standard for the treatment of burn wounds. In a number of cases, treatment with autologous tissue is not possible and skin substitutes are used. The outcome, however, is not optimal and improvements are needed. Inspired by scarless healing in early embryonic development, we here set out a strategy for the design and construction of embryonic-like scaffolds for skin tissue engineering. This strategy may serve as a general approach in the construction of embryonic-like scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(72 reference statements)
2
7
0
Order By: Relevance
“…The approach described by Uijtdewilligen et al 133 highlights the potential to incorporate ECM proteins and growth factors reflective of the fetal milieu into tissue engineering scaffolds. As previously mentioned, increased fibroblast proliferation and migration with rapid wound healing is characteristic of the fetal regenerative response and the increased cellularity and rate of wound closure achieved through stem cell based therapies, whether BM-MSCs or ASCs, partially recapitulates the fetal response to injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach described by Uijtdewilligen et al 133 highlights the potential to incorporate ECM proteins and growth factors reflective of the fetal milieu into tissue engineering scaffolds. As previously mentioned, increased fibroblast proliferation and migration with rapid wound healing is characteristic of the fetal regenerative response and the increased cellularity and rate of wound closure achieved through stem cell based therapies, whether BM-MSCs or ASCs, partially recapitulates the fetal response to injury.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach described by Uijtdewilligen et al involves the incorporation of molecules identified to be upregulated during embryonic skin development, including hyaluronan, into a type I collagen-heparin scaffold. 133 Though McDevitt’s group have not yet assessed the regenerative potential of ESC produced ECM and Uijtdewilligen et al employed only type I collagen and should have prioritized type III collagen, in the authors opinions, these approaches represents a significant step towards recapitulation of the fetal dermal environment.…”
Section: Fetal Vs Adult Wound Healingmentioning
confidence: 99%
“…Mice aged 90 days (90 days post birth [P90]) were used for timed mating and dorsal skin was collected at 14 days (E14) and 16 days after conception (E16). At E14 hair follicle development is initiated, and at E16 this process is almost completed in combination with a stratified epidermis and organized dermis [ 18 , 19 ]. For the RNA samples of E14, dorsal skin of seven embryos from one female was pooled and used for RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, skin from 1-day old pups (P1) and adult mice (P90) was collected. At P1 skin is more organized and has been exposed to air [ 18 , 19 ]. For the two dorsal skin samples for P1, three pups from two females were taken per sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation